Teorie e scoperte sulla nascita umana: il linguaggio rinnovato di Massimo Fagioli negli articoli di “Left” (2016-2017) - De Simone, Gianfranco (Il sogno della farfalla, 2020)
This article thoroughly analyzes the theoretical evolution of Massimo Fagioli’s work, published in the weekly magazine Left. This theoretical development was drawn up starting from the Conference celebrating the 40 years of cure, training and research carried out by Fagioli in the Collective Analysis. After establishing the distinction between discoveries and theoretical ideas, the author focuses on the process leading to the choice of words to write about human birth. This paper shows how Fagioli investigated the root and identity of these words in order to reveal about human origin and identity.